(untitled) (Castilla. Estudios de Literatura, 2020)
Since the extension of Javier Rodríguez Pequeño to the Tomás Albaladejo possible worlds theory, a model of verisimilar fantastic fiction in which some products of our imagination related to the scientific and technological development is considered as possible. Taking the concept of the cognitive strangement by Darko Suvin to define the Science Fiction I will develop the proposal of the uncanny as an inseparable category of this kind of texts (expandable to films and videogames) by using the works of Sigmund Freud, Masahiro Mori and Angela Tinwell among others.